2006
DOI: 10.1108/02683940610643206
|View full text |Cite
|
Sign up to set email alerts
|

Work‐family interference, emotional labor and burnout

Abstract: Purpose-The purpose of the current study is to examine the relationship between emotional display rules/job focused labor, work-family interference (WFI) and burnout among a sample of workers in a Dutch governmental organization. Design/methodology/approach-The research is a cross-sectional study of 174 workers from a Dutch governmental organization. Findings-Emotional display rules and job-focused labor were related to burnout and psychosomatic complaints. More specifically, the need to hide negative emotions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 78 publications
(107 reference statements)
11
78
0
3
Order By: Relevance
“…According to Grandey [36], surface acting involves higher costs and leads to less favorable outcomes than deep acting. Many studies [18,31,34,[38][39][40][41][42][43][44] confirm this hypothesis. At the same time, research findings have shown a positive correlation between deep acting and the feeling of personal accomplishment [31,32,34].…”
Section: Emotional Laborsupporting
confidence: 52%
“…According to Grandey [36], surface acting involves higher costs and leads to less favorable outcomes than deep acting. Many studies [18,31,34,[38][39][40][41][42][43][44] confirm this hypothesis. At the same time, research findings have shown a positive correlation between deep acting and the feeling of personal accomplishment [31,32,34].…”
Section: Emotional Laborsupporting
confidence: 52%
“…In the first, surface acting was a significant predictor of WFC for doctors, but not nurses (Montgomery et al 2005). In the second study in which both surface and deep acting were included, only surface acting was related positively to WFC (Montgomery et al 2006). In the one study relating emotional labor to FWC, a positive correlation between surface acting and FWC was found; deep acting was not considered (Montgomery et al 2005).…”
Section: Integrating the Work-family Interface The Differential Salimentioning
confidence: 98%
“…Thus, it is clear how self-focused emotional labor would tax individuals' energy, and therefore, would constitute a strain-based work demand. Only two studies (Montgomery et al 2005;Montgomery et al 2006) have examined relationships between self-focused emotional labor and work-family conflict. In the first, surface acting was a significant predictor of WFC for doctors, but not nurses (Montgomery et al 2005).…”
Section: Integrating the Work-family Interface The Differential Salimentioning
confidence: 98%
“…Some variables in different studies, have been identified that changes in them used to increase positive emotions this variables include followings: Potential moderators of these relationships include social support (Brotheridge and Lee 2002), situational, interpersonal, and individual factors (Ashforth and Humphrey 1993), role identity (Mann 2004), opportunities to decompress (Montgomery et al 2006), job autonomy (Lewis 2005;Wharton 1993), and the freedom to express emotion (Lively 2000). A discussion of the differences between the fields of nursing and other jobs, related whit this job position and duties of the profession in a hospital, so that that interacting with patients is not part of a nurse's 'legitimate' work (also see Henderson 2001;Smith 1992).…”
Section: Emotional Labor and Nursingmentioning
confidence: 99%